Be close to me and I will be honest: How social distance influences honesty - Daniel Hermann; Andreas Ostermaier (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
We conducted a laboratory experiment to examine how honesty depends on social distance. Participants cast dice and reported the outcomes to allocate money between themselves and fellow students or the socially distant experimenter. They could lie about outcomes to earn more money. We found that dishonesty increases with social distance. However, responsiveness to social distance depends on personal preferences about inequity and honesty as a moral value. We observed selfish "black lies" but not altruistic "white lies" (outcomes were not understated to reduce inequality). Our results suggest that the reduction of social distance can promote honesty in social interactions.
Keywords: C91; D63; D64; 330; cheating; honesty; social distance; experiment